When we were young & brave : a novel - Gaynor, Hazel (William Morrow, an imprint of HarperCollinsPublishers, 2020)
Enduring privation when Japan declares war on England, a teacher at a British missionary school in China is sent to a distant internment camp, where she provides support and instruction to incarcerated children taken from their parents.